Nalar Maqasid al-Syari'ah Rasyid Ridha dalam Tafsir Al-Manar: Studi atas Ayat-Ayat Riba dan Poligami - Saifullah Saifullah (Fakultas Syariah Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2026)
The stagnation of Islamic law has been largely attributed to rigid textualism and taqlīd that disconnects revelation from evolving social realities. This normative-ushuli study aims to examine the maqāṣid al-sharī‘ah paradigm independently developed by Muhammad Rashid Rida in the later volumes of Tafsir Al-Manar (Volumes VI-XII) through content analysis and legal hermeneutics. The findings reveal that Rida constructed a legal epistemology based on a dichotomous distinction between the static sphere of worship (ta‘abbudī) and the dynamic realm of social transactions (ta‘aqqulī). In socio-economic matters, the principle of maslahah mursalah is positioned as a primary methodological instrument for qualifying the general application of hadith āhād. This teleological reasoning is demonstrated in two major cases: the reinterpretation of riba by restricting its absolute prohibition to ribā al-nasī’ah, thereby opening the possibility of re-examining modern banking interest through a maqāṣid-based approach, and the restriction of polygamy through state legal intervention to protect women’s rights and family welfare. The study further demonstrates that the legal paradigm developed in Tafsir Al-Manar possesses significant relevance to contemporary Islamic legal reform, particularly in the fields of family law and Islamic economic law in Indonesia.